Effects of Dialysis Modality on Heart Rate Variability - Ulu, Ramazan; Gozel, Nevzat; Pembegul Yigit, Irem; Kemec, Zeki; Aksoy Ugur, Kader; Dogdu, Orhan; Dogukan, Ayhan (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2017)
OBJECTIVE: Patients with chronic kidney disease have a worse prognosis and carry a high risk of cardiovascular death and in particular sudden cardiac death. Reduced heart rate variability predicted an increased risk of mortality in non-dialysis chronic kidney disease and patients on chronic dialysis treatment. MATERIAL and METHODS: In this sectional study, we analysed heart rate variability of 28 patients with chronic kidney disease on dialysis therapy compared to a healthy control group. Heart rate variability was measured with 24-hour Holter electrocardiography. The results were compared to 30 healthy controls. RESULTS: The patients with chronic kidney disease on dialysis therapy had significantly lower heart rate variability compared to control subjects (for SDNN and pNN50; 95.4 +/- 31.5 vs. 127.5 +/- 38.8; p=0.001 and 8.3 +/- 6.1 vs. 16 +/- 9; p<0.001, respectively). There was no difference in terms of heart rate variability among hemodialysis and peritoneal dialysis modalities (for SDNN and PNN50, 90.7 +/- 32 vs. 102.5 +/- 30.8, p=0.32 and 8.6 +/- 6.3 vs. 7.8 +/- 6, p=0.71, respectively). CONCLUSION: Reduced autonomic function may be one of the factors for cardiovascular events in patients with chronic kidney disease on dialysis therapy. There were no differences between hemodialysis and peritoneal dialysis.
Diyaliz modalitelerinin kalp hizi de?işkenli?i üzerine olan etkisi
Keywords: Heart rate variability; Dialysis modalities; Cardiovascular events